Silver Entrepreneurship Agenda in Malaysia: A Proposed Model for Productive Aging - Nasurdin, Aizzat Mohd; Halim, Hasliza Abdul; Seet, Pishen (Bina Nusantara University, 2012)
This paper aims at proposing a framework for productive aging among those aged 45-plus or retiree via entrepreneurial initiatives, known as ‘silver entrepreneurs’. Evidence has shown that the number of Malaysians aged population is estimated to be more than 1.4 million and is projected to increase to 3.3 million in the year 2020 (Mafauzy, 2000). It is acknowledged that a group of these will comprise of professionals who are aged 45-plus and retirees with relevant industry experience as well as knowledge and well-established networks built up over their working careers which will enable them to effectively identify entrepreneurial opportunities and secure resources efficiently to exploit them. However, there is little research on and understanding of what drives these ‘silver entrepreneurs’, with most of the research, focussed on entrepreneurial ventures started by 18-35 year-olds. This means that policy-makers are ill-equipped to develop specific measures that will assist retirees into a second or sunset career in entrepreneurship. This research aims to bridge the gap by assessing the profile and motivations of silver entrepreneurs in Malaysia with a specific focus on understanding the internal and external factors that affect their intentions to start new ventures as well as factors that affect the success and growth of these ventures.